Insights Into Fault‐Magma Interactions in an Early‐Stage Continental Rift From Source Mechanisms and Correlated Volcano‐Tectonic Earthquakes. Issue 4 (26th February 2019) - Oliva, S. J.; Ebinger, C. J.; Wauthier, C.; Muirhead, J. D.; Roecker, S. W.; Rivalta, E.; Heimann, S.
Abstract: Strain in magmatic rifts is accommodated by both faulting and dike intrusion, but little is known of the frequency of dike intrusions in early‐stage rifts. We use a new earthquake data set from a dense temporary seismic array (2013–2014) in the ~7‐Myr‐old Magadi‐Natron‐Manyara section of the East African Rift, which includes the carbonatitic Oldoinyo Lengai volcano that erupted explosively in 2007–2008. Full moment tensor analyses were performed on M  > 3.4 earthquakes (0.03‐ to 0.10‐Hz band) that occurred during the intereruptive cycle. We find two opening crack‐type and various non‐double‐couple earthquake source mechanisms and interpret these as fluid‐involved fault rupture. From waveform analysis on the nearest permanent seismic station, we conclude that similar rupture processes probably occur over eruptive and intereruptive cycles. The repeated and dynamically similar fluid‐involved seismicity, along with intrabasinal localization of active deformation, suggests that significant and persistent strain is accommodated by magmatic processes, modulated by tectonic cycles. Plain Language Summary: How do Earth's plates deform between volcanic eruptions and after plate tectonic stresses have been released in large earthquakes? Simulations of earthquake rupture in rift zones where the plates are diverging tell us that opening + shearing cracks created several of the moderate earthquakes. The opening may be due to magmatic fluids and gases from crustal magma reservoirs. We also compare the earthquake signals to those from the past 20 years and find that these magma‐related earthquakes are frequent occurrences at least in the past 10 years. Magmatic processes contribute to the short time scale cycles of plate boundary deformation in rift zones. Key Points: Non‐double‐couple earthquakes are observed in an early‐stage rift and interpreted as fluid‐involved faulting above a sill complex Earthquakes in 2013–2014 have similar driving mechanisms as the fault‐dike‐eruption episode in 2007–2008 but did not rupture the same faults Magma‐involved faulting persistently accommodates strain over intereruptive cycles